Burden of Aortic Aneurysm and Its Attributable Risk Factors from 1990 to 2019: An Analysis of the Global Burden of Disease Study 2019 - Wang, Zhuo; You, Yayu; Yin, Zhehui; Bao, Qinyi; Lei, Shuxin; Yu, Jiaye; Xie, Cuiping; Ye, Feiming; Xie, Xiaojie (Frontiers in Cardiovascular Medicine, 2022)
Background Global and national estimates on the epidemiology of aortic aneurysms are prerequisites for disease management and policymaking. Based on the Global Burden of Disease (GBD) 2019, this study aimed to discern the global aortic aneurysm burden by systematically analyzing demographic data on mortality and exploring the attributable risks and relevant factors. Methods The data analyzed in this study were available in the Global Health Data Exchange (GHDx) online query tool. The population in our study comprised individuals from 204 countries and territories from 1990 to 2019. The estimated annual percentage changes (EAPCs) were performed to assess the temporal trends of aortic aneurysms and their attributable risks. Spearman correlation analysis was performed to explore the relationship between the burden of aortic aneurysm and covariates. Results Although aortic aneurysm-related deaths (82.1%) and disability-adjusted life years (DALYs) (67%) increased from 1990 to 2019, the global trend of age-standardized rate of death (ASRD) (EAPC: −1.34, 95% CI = −1.46 to −1.22, P < 0.001) and age-standardized rate of DALY (ASDALYR) (EAPC: −1.06, 95% CI = −1.17 to −0.95, P < 0.001) decreased, both of which presented age dependence and gender differences. Smoking and high systolic blood pressure (SBP) were the main attributable risks of disease burden and tend to decease globally (EAPC: −1.89, 95% CI = −2.03 to −1.89, P < 0.001; −1.31 95% CI = −1.43 to −1.19, P < 0.001, respectively). Alcohol abstinence (male: R = −0.71, P < 0.001; female: R = −0.73, P < 0.001), smoking age of initiation (male: R = −0.32, P < 0.001; female: R = −0.50, P < 0.001), physical activity (male: R = −0.50, P < 0.001; female: R = −0.55, P < 0.001), and mean temperature (R = −0.62, P < 0.001) had negative correlation with ASRD. However, cholesterol level (male: R = 0.62, P < 0.001; female: R = 0.39, P < 0.001), body mass index (BMI) (male: R = 0.30, P < 0.001; female R = −0.01, P > 0.05), and alcohol consumption (male: R = 0.46, P < 0.001; female: R = 0.42, P < 0.001) had a positive correlation with ASRM. Besides, standard of living and medical resources positively related to burden of aortic aneurysm. Conclusion In this study, a decreasing trend of aortic aneurysm burden was found globally, especially in advanced regions. Aged men who smoke and women who have hypertension should pay close attention to, particularly in deprived economic groups, and many approaches can be performed to reduce the burden of aortic aneurysms.